Samuel Dominic Chukwuemeka (SamDom For Peace)

For in GOD we live, and move, and have our being. - Acts 17:28

The Joy of a Teacher is the Success of his Students. - Samuel Chukwuemeka

Solved Examples - Simplify Radicals

For ACT Students
The ACT is a timed exam...$60$ questions for $60$ minutes
This implies that you have to solve each question in one minute.
Some questions will typically take less than a minute a solve.
Some questions will typically take more than a minute to solve.
The goal is to maximize your time. You use the time saved on those questions you solved in less than a minute, to solve the questions that will take more than a minute.
So, you should try to solve each question correctly and timely.
So, it is not just solving a question correctly, but solving it correctly on time.
Please ensure you attempt all ACT questions.
There is no "negative" penalty for any wrong answer.

Simplify the radicals completely
Express your answer in terms of $i$.

(1.) $\sqrt {-144}$


$ \sqrt {-144} \\[3ex] = \sqrt{-1} * \sqrt{144} \\[3ex] = i * 12 \\[3ex] = 12i $
(2.) $\sqrt {-21}$


$ \sqrt {-21} \\[3ex] = \sqrt{-1} * \sqrt{21} \\[3ex] = i * \sqrt{21} \\[3ex] = i\sqrt{21} $
(3.) $-\sqrt {-75}$


$ -\sqrt {-75} \\[3ex] = -1 * \sqrt{-75} \\[3ex] = - 1* \sqrt{-1} * \sqrt{75} \\[3ex] = -1 * i * \sqrt{25 * 3} \\[3ex] = -i * \sqrt{25} * \sqrt{3} \\[3ex] = -i * 5 * \sqrt{3} \\[3ex] = -5i\sqrt{3} $
(4.) $-\sqrt {-53}$


$ -\sqrt {-53} \\[3ex] = -1 * \sqrt{-1} * \sqrt{53} \\[3ex] = - 1* i * \sqrt{53} \\[3ex] = -i\sqrt{53} $
(5.) $\sqrt {-150}$


$ \sqrt {-150} \\[3ex] = \sqrt{-1} * \sqrt{150} \\[3ex] = i * \sqrt{25 * 6} \\[3ex] = i * \sqrt{25} * \sqrt{6} \\[3ex] = i * 5 * \sqrt{6} \\[3ex] = 5i\sqrt{6} $
(6.) $\sqrt{\dfrac{-49}{75}}$


$ \sqrt{\dfrac{-49}{75}} \\[5ex] = \sqrt {\dfrac{-1 * 49}{75}} \\[5ex] = \sqrt{-1} * \sqrt{\dfrac{49}{75}} \\[5ex] = i * \dfrac{\sqrt{49}}{\sqrt{75}} \\[5ex] = i * \dfrac{7}{\sqrt{25 * 3}} \\[5ex] = i * \dfrac{7}{\sqrt{25} * \sqrt{3}} \\[5ex] = i * \dfrac{7}{5 * \sqrt{3}} \\[5ex] = \dfrac{7i}{5\sqrt{3}} \\[5ex] = \dfrac{7i}{5\sqrt{3}} * \dfrac{\sqrt{3}}{\sqrt{3}} \\[5ex] = \dfrac{7i\sqrt{3}}{5\sqrt{3}*\sqrt{3}} \\[5ex] = \dfrac{7i\sqrt{3}}{5(3)} \\[5ex] = \dfrac{7i\sqrt{3}}{15} \\[5ex] $
(7.) $(\sqrt {-36})(\sqrt{-4})$


$ (\sqrt {-36})(\sqrt{-4}) \\[3ex] = (\sqrt{-1 * 36})(\sqrt{-1 * 4}) \\[3ex] = \sqrt{-1} * \sqrt{36} * \sqrt{-1} * \sqrt{4} \\[3ex] = i * 6 * i * 2 \\[3ex] = i^2 * 12 \\[3ex] = -1 * 12 \\[3ex] = -12 $
(8.)


$ -2\left|3 - \dfrac{p}{3}\right| + 1 = -5 \\[5ex] -2\left|3 - \dfrac{p}{3}\right| = -5 - 1 \\[5ex] -2\left|3 - \dfrac{p}{3}\right| = -6 \\[5ex] \left|3 - \dfrac{p}{3}\right| = \dfrac{-6}{-2} \\[5ex] \left|3 - \dfrac{p}{3}\right| = 3 \\[5ex] This\:\: means\:\: that \\[5ex] 3 - \dfrac{p}{3} = 3 \:\:OR\:\: -(3 - \dfrac{p}{3} = 3 \\[5ex] 3 - \dfrac{p}{3} = 3 \\[5ex] 3 - 3 = \dfrac{p}{3} \\[5ex] 0 = \dfrac{p}{3} \\[5ex] \dfrac{p}{3} = 0 \\[5ex] p = 0(3) \\[3ex] p = 0 \\[3ex] OR \\[3ex] -(3 - \dfrac{p}{3} = 3 \\[5ex] Divide\:\: both\:\: sides\:\: by\:\: -1 \\[3ex] 3 - \dfrac{p}{3} = -3 \\[5ex] 3 + 3 = \dfrac{p}{3} \\[5ex] 6 = \dfrac{p}{3} \\[5ex] \dfrac{p}{3} = 6 \\[5ex] p = 6(3) \\[3ex] p = 18 \\[3ex] $ Check
Check for both values.
$ \underline{LHS} \\[3ex] -2\left|3 - \dfrac{p}{3}\right| + 1 \\[5ex] p = 0 \\[3ex] -2\left|3 - \dfrac{0}{3}\right| + 1 \\[5ex] -2|3 - 0| + 1 \\[5ex] -2|3| + 1 \\[3ex] -2(3) + 1 \\[3ex] -6 + 1 \\[3ex] -5 \\[3ex] $ $p = 0$ is a solution




$ -2\left|3 - \dfrac{p}{3}\right| + 1 \\[5ex] p = 18 \\[3ex] -2\left|3 - \dfrac{18}{3}\right| + 1 \\[5ex] -2|3 - 6| + 1 \\[5ex] -2|-3| + 1 \\[3ex] -2(3) + 1 \\[3ex] -6 + 1 \\[3ex] -5 \\[3ex] $ $p = 18$ is a solution
$ \underline{RHS} \\[3ex] -5 $